2000
DOI: 10.1016/s1044-0305(00)00183-5
|View full text |Cite
|
Sign up to set email alerts
|

Observation of amide anions in solution by electrospray ionization mass spectrometry

Abstract: Negative quasimolecular ions of aromatic carboxylic acid amides have been observed unexpectedly under electrospray ionization conditions. Hypothetically, deprotonation of either carboxamide or carboximidic acid tautomers can produce anions with equivalent resonance structures, the stability of which is affected by conjugated aromatic substituents. In this study, a series of meta and para substituted benzamides were analyzed using electrospray ionization mass spectrometry in aqueous methanolic solutions. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 6 publications
0
22
1
Order By: Relevance
“…This would explain why the ESI response of the analytes studied here, all of which have pKa values less than 10, is not entirely dependent on pKa. This would also explain why the results presented here are different than that of Chiu and Lo, who observed a dependency in°ESI-response°on°acidity°of°various°amides° [11].°The pKa values of the amides are much higher than those for the analytes used in this study. The predicted increase in solution pH for negative ionization ESI-MS has yet to be observed experimentally, and in fact, results of a study by Zhou et al indicated a possible decrease in pH in evaporating droplets formed by negative°ion°ESI-MS° [19].°However,°Zhou°et°al.°did°suggest that the apparent decrease in pH observed in their experiments may have occurred only in the larger parent droplets, and that the offspring droplets formed in the ESI-MS process (the ones that eventually form ions) may, indeed, decrease in pH due to enrichment in OH Ϫ ions.…”
Section: Effect Of Analyte Aciditycontrasting
confidence: 85%
See 1 more Smart Citation
“…This would explain why the ESI response of the analytes studied here, all of which have pKa values less than 10, is not entirely dependent on pKa. This would also explain why the results presented here are different than that of Chiu and Lo, who observed a dependency in°ESI-response°on°acidity°of°various°amides° [11].°The pKa values of the amides are much higher than those for the analytes used in this study. The predicted increase in solution pH for negative ionization ESI-MS has yet to be observed experimentally, and in fact, results of a study by Zhou et al indicated a possible decrease in pH in evaporating droplets formed by negative°ion°ESI-MS° [19].°However,°Zhou°et°al.°did°suggest that the apparent decrease in pH observed in their experiments may have occurred only in the larger parent droplets, and that the offspring droplets formed in the ESI-MS process (the ones that eventually form ions) may, indeed, decrease in pH due to enrichment in OH Ϫ ions.…”
Section: Effect Of Analyte Aciditycontrasting
confidence: 85%
“…Only a few studies have previously been carried out that have attempted to correlate polarity and acidity with responsiveness in negative ion ESI-MS. Chiu and Lo studied negative ionization ESI response of substituted amides, considering primarily the acidity of these compounds [11]. Most amides are not acidic in aqueous solutions; thus, only a few pKa values were available for the amides evaluated.…”
mentioning
confidence: 99%
“…Deprotonation of amides has been reported previously [58]; the imidic acid structure of the corresponding c ion [12] could have made deprotonation even easier. The neutral loss of HN=C(NH 2 ) 2 is proposed to involve the nucleophilic attack of C δ atom by the negatively charged oxygen of the C-terminal carboxyl group.…”
Section: ) P -mentioning
confidence: 84%
“…For mass-spectrometric monitoring of carboxamides, the positive-ion-generating mode is generally preferred because the carboxamide moiety readily undergoes protonation under electrospray ionization conditions. However, it has been demonstrated that carboxamides synthesized from primary amines can be deprotonated under negative-ion electrospray [24] and OH − chemical-ionization conditions [25][26][27]. Herein, we report that under HePI conditions, carboxamides undergo O 2 -• adduct formation and/or deprotonation, and we discuss the significance of the chemical nature of the N-H functionality for the O 2 -• attachment.…”
Section: Introductionmentioning
confidence: 92%